Colorectal Cancer Screening Patient Navigation for Patients with Mental Illness and/or Substance Use Disorder: Pilot Randomized Control Trial. Issue 4 (1st October 2020) - Abuelo, Carolina; Ashburner, Jeffrey M.; Atlas, Steven J.; Knudsen, Amy; Morrill, James; Corona, Patricia; Shtasel, Derri; Percac-Lima, Sanja
Abstract: Objective: Colorectal cancer (CRC) is the second leading cause of cancer death in the US. Screening has decreased CRC mortality. However, disadvantaged patients, particularly those with mental illness or substance use disorder (SUD), are less likely to be screened. The aim of this trial was to evaluate the impact of a patient navigation program on CRC screening in patients with mental illness and/or SUD. Methods: A pilot randomized nonblinded controlled trial was conducted from January to June 2017 in an urban community health center serving a low-income population. We randomized 251 patients aged 50–74 years with mental illness and/or SUD diagnosis overdue for CRC screening to intervention ( n  = 126) or usual care ( n  = 125) stratified by mental illness, SUD, or dual diagnosis. Intervention group patients received a letter followed by a phone call from patient navigators. Navigators helped patients overcome their individual barriers to CRC screening including: education, scheduling, explanation of bowel preparation, lack of transportation or accompaniment to appointments. If patient refused colonoscopy, navigators offered fecal occult blood testing. The main measure was proportion of patients completing CRC screening in intervention and usual care groups. Results: Navigators contacted 85 patients (67%) in the intervention group and 26 declined to participate. In intention-to treat analysis, more patients in the intervention group received CRC screening than in the usual care group, 19% versus 10.4% ( p = .04). Among 56 intervention patients who received navigation, 19 completed screening (33.9% versus 10.4% in the control group, p = .001). In the subgroup of patients with SUD, 20% in the intervention group were screened compared to none in the usual care group ( p = .05). Conclusions: A patient navigation program improved CRC screening rates in patients with mental illness and/or SUD. Larger studies in diverse care settings are needed to demonstrate generalizability and explore which modality of CRC screening is most acceptable and which navigator activities are most effective for this vulnerable population. Trials Registration Number: 2016P001322